2022
DOI: 10.3389/fphys.2022.932596
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock disruptions link oxidative stress and systemic inflammation to metabolic syndrome in obstructive sleep apnea patients

Abstract: Objectives: Obstructive sleep apnea (OSA) is an independent risk factor for metabolic syndrome (MetS). Recent studies have indicated that circadian clock genes were dysregulated in OSA. In addition, it is clear that the impairment of circadian clocks drives the progression of MetS. Therefore, we hypothesized that circadian rhythm disruption links OSA with MetS.Methods: A total of 118 participants, who underwent polysomnography (PSG) and were diagnosed as healthy snorers (control, n = 29) or OSA (n = 89) patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…9 At the population level, the expression of Bhlhe40 was positively correlated with IL-6 and total oxidant status levels and negatively related to total antioxidant status levels. 10 In vitro observation showed an elevated proliferation and a declined apoptosis of pulmonary arterial endothelial cells under hypoxia conditions by the upregulation of Bhlhe40. 12 Conversely, our previous studies found a low expression in high glucose-treated VSMCs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…9 At the population level, the expression of Bhlhe40 was positively correlated with IL-6 and total oxidant status levels and negatively related to total antioxidant status levels. 10 In vitro observation showed an elevated proliferation and a declined apoptosis of pulmonary arterial endothelial cells under hypoxia conditions by the upregulation of Bhlhe40. 12 Conversely, our previous studies found a low expression in high glucose-treated VSMCs.…”
Section: Discussionmentioning
confidence: 98%
“…9 A recent study demonstrated that the high expression of Bhlhe40 was relevant to IR in patients with obstructive sleep apnea and can be utilized for predicting the presence of metabolic syndrome in obstructive sleep apnea individuals. 10 Moreover, chronic inflammation and oxidative stress are two major hallmarks of atherosclerosis. 11 At the cellular level, overexpression of Bhlhe40 upregulated the generation of reactive oxygen species and the expression of pro-inflammatory cytokines, such as interleukin 6 (IL-6), IL-1β, tumour necrosis factor alpha, and monocyte chemoattractant protein-1 in pulmonary arterial smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…DEC1 expression was a predictor of metabolic syndrome in OSA patients and was associated with increased levels of IL‐6. Therefore, the authors postulated DEC1 as a biomarker of OSA‐associated metabolic syndrome (X. Li et al, 2022). However, as circadian gene expression was only evaluated at a single time‐point (morning fasting blood sample), the study did not evaluate circadian oscillation patterns.…”
Section: Review On Circadian System Sleep Disordersmentioning
confidence: 99%
“…In this model, the circadian system exerts an influence on respiratory events in obstructive sleep apnea (Butler et al, 2015), while OSA dysregulates the circadian system mainly through sleep fragmentation and intermittent hypoxia (HIF‐1 signalling) (Gabryelska, Sochal, et al, 2020; Manella et al, 2020; Noda et al, 2000). Dysregulation of circadian rhythms contributes to alterations in various homeostatic processes, which are involved in the development of OSA‐related comorbidities, such as metabolic syndrome (X. Li et al, 2022), cardiovascular disease (Noda et al, 1998), and cancer (Hunyor & Cook, 2018). With further research, the endogenous circadian system might prove a potential target for OSA treatment, especially for severe OSA and OSA‐related comorbidities that show poor response to CPAP (Moreira et al, 2017).…”
Section: Review On Circadian System Sleep Disordersmentioning
confidence: 99%
See 1 more Smart Citation